ARTIKULASI IDENTITAS WONG SOLO DI EKS ENKLAVE SURAKARTA: KONSTRUKSI BAHASA DAN PEMERTAHANANNYA - Sulistyowati . (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Culturally Kotagede and Imogiri consist of the ex enclave regions of Surakarta which are called Kotagede SK and Imogiri SK. The community of the ex Surakarta enclave is also known as Wong Solo. This article describes the existence of Wong Solo in Surakarta ex enclave in maintaining its identities. The label of priyayi, courteous, alus, glamorous, and umuk attached to Wong Solo articulated through language practices and material culture. Historical and sociocultural perspective used to describe the verbal expression as identity markers and narratives elicited through etnographic work. It is assumed that the romanticism of the elite, class consciousness, and awareness of the preservation of tradition dominate retention Wong Solo. Cultural agencies, Surakarta and Yogyakarta Palace in the historical affinity presented by abdi dalem juru kunci of the kings of Mataram cemetery become binding factor of Wong Solo identity in Surakarta ex enclave.